A rare deleterious missense mutation in the AXIN2 gene in Chinese women with polycystic ovary syndrome - Ying Zhang; Yu Chen; Fa-Ying Liu; Jing-Wen Fu; Xian-Xian Liu; Jun Tan; Ou-Ping Huang; Yang Zou (Gynecological Endocrinology)
Background Polycystic ovary syndrome (PCOS) is an endocrine disorders and characterized by polycystic ovary morphology and oligomenorrhea, affecting fertility and health condition of female around the world. The causative factors of PCOS are complex, and genetic structure remains a long-standing medical challenge in genetics. Previous genome-wide association study (GWAS) showed that Wing-less-related integration site (Wnt) signaling is the most affected pathway among PCOS-related risk genes, and genetic mutations in the Wnt/β-catenin signaling may lead to abnormal development of PCOS.Objective To explore the possibility of axis inhibitor-2 (AXIN2) variants in Chinese women with PCOS and assess their pathogenicities.Methods A total of 365 Chinese women with PCOS and 905 women without PCOS as control were recruited from Jiangxi Provincial Maternal and Child Health Hospital, All of the 11 exons and flanking regions of the AXIN2 gene were amplified by polymerase chain reaction (PCR), the potential variants were analyzed by Sanger sequencing. The evolutionary conservation analysis of the identified Axin-2 mutant was analyzed among 15 vertebrates from human to zebrafish. The protein structure change was analyzed between the wild-type and mutation-type. The pathogenicity of AXIN2 variant was further analyzed in silico.Results We totally identified 7 genetic variants of AXIN2 in this study, including 4 synonymous and 3 missense. Among them, we find a rare deleterious missense variant [p.R714W (c.2140C > T)]. The allele frequencies of this variant were 0.82% and 0.17% in PCOS cases and matched controls, respectively. And it was ranging from 7.89e-5 to 1.47e-4 in public databases. Fisher’s exact test indicated that the allele frequencies in PCOS were p < 0.05 compared to both the controls and the databases. Especially, the mutant amino acid site is highly conserved in vertebrates, while the mutation changed the 714th arginine to tryptophan resulting in significant change in the protein structural of Axin-2.Conclusion In this study, we identified a rare deleterious missense AXIN2 mutation [p.R714W (c.2140C > T)] in Chinese women with PCOS, and this mutant is probably pathogenic. This study may provide a new perspective on revealing the genetic variation of PCOS.